2017
DOI: 10.1007/s10518-017-0228-1
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic tensile-compressive tests on thin concrete boundary elements with a single layer of reinforcement prone to out-of-plane instability

Abstract: Cyclic tensile-compressive tests of thin concrete boundary elements with a single layer of reinforcement prone to out-of-plane instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 7 publications
0
15
0
1
Order By: Relevance
“…This has become a popular form of experimental testing in recent years (e.g. [13][14][15][16][17][18]) and is commonly referred to as 'prism testing'. This form of testing allows for the performance of various RC wall end region detailing techniques to be experimentally assessed for different failure mechanisms (e.g.…”
Section: Testing Methodology and Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…This has become a popular form of experimental testing in recent years (e.g. [13][14][15][16][17][18]) and is commonly referred to as 'prism testing'. This form of testing allows for the performance of various RC wall end region detailing techniques to be experimentally assessed for different failure mechanisms (e.g.…”
Section: Testing Methodology and Backgroundmentioning
confidence: 99%
“…The prism testing performed in literature currently includes: 9 specimens tested by Patel et al [13], which were small specimens with one central bar; 1 specimen tested by Segura et al [14], which was a ductile prism specimen with a small height-to-thickness ratio of 6.0; 16 specimens tested by Taleb et al [15], which were all ductile prism specimens with small to moderate height-to-thickness ratios of 5.4 to 8.8; 33 specimens tested by Welt et al [16], which included both non-ductile and ductile prism specimens with small to moderate height-to-thickness ratios of 4.0 to 8.9, however only 1 non-ductile specimen was tested under cyclic actions with the others under monotonic loading; 8 specimens test by Hilson [17], which were all non-ductile prism specimens with a small height-to-thickness ratio of 5.0; and 12 specimens tested by Rosso et al [18], which were non-ductile specimens with central reinforcement and very slender height-to-thickness ratios of 24 to 30. The studies by Hilson [17] and Rosso et al [18] represent the best test programs identified in literature for non-ductile boundary elements. The test specimens in this study have different reinforcement configurations and height-to-thickness ratios than the specimens in [17,18], in addition to also including specimens that are constructed with lap splices of the vertical reinforcement and using precast grout tube connections, both of which are commonly detailing aspects of non-ductile walls.…”
Section: Testing Methodology and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2010 Chile and 2011 Christchurch earthquakes, out‐of‐plane instability was observed in some slender RC shear walls including L‐shaped walls, which was an uncommon failure mode for concrete walls and raised concerns about the global instability of slender RC walls. The parameters governing the out‐of‐plane failure of RC walls could be obtained by cyclic tensile‐compressive tests on boundary elements and modified with experiments on RC shear walls under in‐plane cyclic loading . Furthermore, relevant analytical models and finite element models for out‐of‐plane instability were developed and subsequently verified with experimental results, demonstrating that these numerical models were able to predict the out‐of‐plane deformation as well as the ultimate failure mode due to out‐of‐plane instability .…”
Section: Introductionmentioning
confidence: 99%
“…Rosso et al studied the parameters affecting the out‐of‐plane response of singly reinforced walls using cyclic tensile‐compressive tests on the corresponding boundary elements. Haro et al included bidirectional loading protocols in the RC prism testing and scrutinized the effect of the longitudinal reinforcement ratio on the onset of out‐of‐plane instability in planar walls.…”
Section: Introductionmentioning
confidence: 99%